Impact of the EU regulations on the payment services - Korus, Krzysztof (Ekonomia i Prawo. Economics and Law, 2024)
Abstract Motivation: Legislation in payment services domain is broad, exhaustive, and detailed. Fostering innovation is one of several primary goals of the legislation. The impact of a series of regulations on the payments market, particularly the Second Payment Services Directive (PSD2), requires a comprehensive assessment of their effects on legislative efficiency and the development of European payment service providers. Aim: The paper aims to explore the vectors and strength of the impact of EU payments legislation on the market for payment services with a focus on innovation. Results: The major impact vector of the payment legislation is stimulating the supply of payment services. An important instrument in this domain is standardization and interoperability with legislation on open banking (PSD) and Single Euro Payment Area being flagship use – cases of such instrument. Open banking legislation (standardization) resulted in the development of a new class of services unlocking new value for demand side. SEPA legislation (interoperability) resulted in availability of significantly more efficient and productive flows of funds within the EU. In both use – cases the impact vectors demonstrate strong feedback and positive reinforcement. Instant payments developed on the building blocks of SEPA enable open banking account – to - account payments to compete with payment cards and similar instruments with acquirers being able to narrow down substantially the risks they are exposed to when engaging in traditional merchant payments. Open banking payments in turn stimulate SEPA payments. Altogether the use case of EU SEPA and open banking legislation proves that legislation addressing interoperability and standardization is paramount to steer payment market towards mutually reinforced innovation. Careful consideration and selection of policy mix in this domain results in highly efficient transmission mechanism.